2003
DOI: 10.1111/j.1151-2916.2003.tb03483.x
|View full text |Cite
|
Sign up to set email alerts
|

Cubic‐Formation and Grain‐Growth Mechanisms in Tetragonal Zirconia Polycrystal

Abstract: The microstructure in Y 2 O 3 -stabilized tetragonal zirconia polycrystal (Y-TZP) sintered at 1300°-1500°C was examined to clarify the role of Y 3؉ ions on grain growth and the formation of cubic phase. The grain size and the fraction of the cubic phase in Y-TZP increased as the sintering temperature increased. Both the fraction of the tetragonal phase and the Y 2 O 3 concentration within the tetragonal phase decreased with increasing fraction of the cubic phase. Scanning transmission electron microscopy (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 10 publications
11
115
0
10
Order By: Relevance
“…By comparing the grain structure seen in the SEM image with the elemental maps, one can see that the yttrium segregation into LYR and HYR domains occurs in a grain-wise fashion. There is no clear suggestion of localization at grain boundaries as suggested by Schelling et al 13 Yttrium has a low solubility in the tetragonal zirconia crystal structure 13 , so the excess yttrium tends to accumulate in the cubic phase. The titanium distribution is rather homogeneous as compared to yttrium, which is expected as titanium solubility in tetragonal zirconia is higher than 5 mol%.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…By comparing the grain structure seen in the SEM image with the elemental maps, one can see that the yttrium segregation into LYR and HYR domains occurs in a grain-wise fashion. There is no clear suggestion of localization at grain boundaries as suggested by Schelling et al 13 Yttrium has a low solubility in the tetragonal zirconia crystal structure 13 , so the excess yttrium tends to accumulate in the cubic phase. The titanium distribution is rather homogeneous as compared to yttrium, which is expected as titanium solubility in tetragonal zirconia is higher than 5 mol%.…”
Section: Resultsmentioning
confidence: 82%
“…Typical powder processed Y-TZP generally has submicron grains as well as an inhomogeneous Y 2 O 3 distribution. 13 Since small grains tend to F o r P e e r R e v i e w 3 suppress the martensitic transformation, when such polycrystals are subjected to applied stress, cracks are generally initiated before achieving observable shape deformation via the transformation. On the other hand, in our recent work 14 , we showed that for small-volume samples with a length scale reduced to a few micrometers, zirconia ceramics will have an oligocrystalline structure and can exhibit significantly enhanced shape memory properties without cracking.…”
Section: Introductionmentioning
confidence: 99%
“…To support this idea, the progressive development of a bimodal grain distribution can be appreciated from micrographs, which is often observed in Y-TZP after long sintering times or at higher temperatures [43]. Nonetheless, with these sintering conditions we are still far from the equilibrium and the conversion from tetragonal to cubic phase needs the formation of highly concentrated regions where the tetragonal distortion is reduced enough to nucleate the new phase [44]. Hence, the amount of cubic phase will be sensitive to the sintering time at this temperature [45,46].…”
Section: Ceo 2 Profiles and Microstructural Aspectsmentioning
confidence: 99%
“…The physical characteristics of barium-titanate ceramics were shown to be size dependent [1][2][3][4], and the Ba/Ti ratio was found to determine the grain growth mechanism [5,6]. At the same time, as was shown in [7][8][9], the relation between the elements in the ceramic interface regions may substantially differ from that in the bulk, which can result in both phase transformation and new phase formation. There may form, for example, a cubic-phase layer in the interface regions of polycrystalline tetragonal ceramics BaTiO 3 [10], a BaCO 3 phase as a result of interaction with atmospheric CO 2 on heating [11], and a glass phase in the interface areas of segnetoelectrical ceramics [12].…”
Section: Introductionmentioning
confidence: 92%